PENGARUH KESADARAN MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK PADA KONSUMEN LE MINERALE DI BANJARMASIN - Muhammad Rifsan Jani; Novia Nour Halisa; Saladin Ghalib; Humaidi (Business Administration, FISIP ULM, 2025)
This study was conducted to determine and examine the partial effect of Brand Awareness on Brand Loyalty among Le Minerale consumers in Banjarmasin; to determine and examine the partial effect of Brand Trust on Brand Loyalty among Le Minerale consumers in Banjarmasin; and to determine and examine the simultaneous effect of Brand Awareness and Brand Trust on Brand Loyalty among Le Minerale consumers in Banjarmasin. This research used a quantitative approach with an explanatory research design. The study was conducted in Banjarmasin. The population consisted of consumers who had consumed Le Minerale at least twice a month. A total of 100 respondents were selected using the accidental sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression analysis with SPSS version 26. The results of the study indicate that Brand Awareness has a significant partial effect on Brand Loyalty among Le Minerale consumers in Banjarmasin. Brand Trust also has a significant partial effect on Brand Loyalty among Le Minerale consumers in Banjarmasin. Furthermore, Brand Awareness and Brand Trust simultaneously have a significant effect on Brand Loyalty among Le Minerale consumers in Banjarmasin